Astronomy in renaissance art - Livio, Mario (Vitruvian Cogitationes, 2022)
What is the importance of presenting, explaining and conceptualizing the sky as a phenomenon of nature in the midst of Renaissance works of art? In this study are presented some artistic constructs of the Renaissance that are described in detail. This was necessary to build a set of knowledge that can be used dialogically in the middle of processes of knowledge transmission related to Astronomy.